Analisis Elastisitas dan Tax Effort Pajak Hotel terhadap Produk Domestik Regional Bruto (PDRB) di Kabupaten Murung Raya - Erwin Erlina; Saipudin Saipudin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This research aims to see whether tax efforts to collect hotel taxes are strong or weak and the elasticity of hotel tax revenue in GRDP in Murung Raya Regency. This research uses quantitative descriptive methods and secondary data for 2011-2019 available from the Regional Revenue Agency or sources related to the research conducted.So that the results are seen from the side of the hotel tax revenue ratio, which includes a strong group in paying taxes on average 1.09, so the tax can be utilized optimally. For the level of elasticity to get results in the form of inelastic seen from the value obtained at <1, it means that the government in Murung Raya Regency is less able to optimize the existing tax potential.